Analisis Perubahan Penutup Lahan di Kecamatan Monano, Kabupaten Gorontalo Utara Menggunakan Data Esri Sentinel-2 Land Cover Multitemporal - Eki Nurhadi Modanggu; Sri Maryati; Moch.Rio Pambudi (-, 2026)
This study aims to analyze land cover dynamics in Monano District, North Gorontalo Regency, using Esri Sentinel-2 Land Cover data for the 2022–2025 period. The data used consisted of ready-to-use land cover products derived from Sentinel-2 imagery. The research methods included data collection, clipping based on the administrative boundaries of the study area, identification of land cover classes, calculation of the area and percentage of each class, and analysis of proportional changes between years. The land cover classes analyzed consisted of water bodies, trees, bare ground, and grass. The results showed that the tree class was the dominant land cover during most of the observation period. In 2025, the tree class covered 84.65 ha or 59.18% of the study area, while the grass class covered 12.28 ha or 8.58%. The largest proportional changes occurred in the grass class, which decreased from 41.18% to 8.58%, and the tree class, which increased from 39.37% to 59.18%. These findings indicate that Esri Sentinel-2 Land Cover data can be utilized as a preliminary source of information for monitoring multitemporal land cover dynamics.